Sleep dissorders and legal drugs and marijuana consumption in university students of Lambayeque region, 2022 - Morales-Ramirez, Sofia Mariagracia (2025)
Introduction: The situation of drug consumption in university students shows an alarming trend, and, delving into the prevalence of sleep disorders, it has been proposed as a research objective to evaluate the statistical association between sleep disorder and the consumption of legal and illegal drugs in the region. Method: descriptive, observational, quantitative, cross-sectional, quantitative study, which contemplates as population the university students of the Lambayeque region. The variables considered were: sex, age, university of origin, year of studies, professional school, alcohol consumption, tobacco consumption, marijuana consumption and sleep disorder. The ASSIST v3.1, Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale and Insomnia Severity Index questionnaires were taken into account. Results: a final sample of 355 students was taken. Fifty-five point two percent of the participants belonged to the female gender. Students from the Señor de Sipan University and the Human Medicine course predominated, with figures of 34.1% and 48.2%, respectively. Of the students, 63.9% had poor sleep quality, and insomnia was the most frequent disorder, representing 61.7% of the total number of participants. Regarding drug use, all participants reported alcohol use; 41.1%, tobacco use; and 19.4%, marijuana use. The female gender predominated in all variables, except tobacco use. In addition, significant associations were only found between tobacco or marijuana use and poor sleep quality. Conclusions: A significant association was demonstrated between tobacco or marijuana use and sleep quality, sleepiness and insomnia.